The Influence of Biofertilizers and Water Content on the Growth and Production of Soybean Plants of Dena-1 Variety - Andriani Eko Prihatiningrum; Muhammad Alif (Nabatia, 2020)
This study aims to determine the effect of biological fertilizers and moisture content on the growth and production of soybean varieties Dena-1. Held in the Laboratory and Greenhouse of the Faculty of Science and Technology, Muhammadiyah University of Sidoarjo, to coincide from February to April 2020. Experiments were arranged factorial in a completely randomized design with three replications. The first factor is the application of biological fertilizers consisting of: without microorganisms, mycorrhizae, Trichoderma, and mycorrhizae and Trichoderma; while the second factor is the ground water content consisting of 20%, 10%, and 5%. The variables observed were plant height, stem diameter, number of pods, number of seeds, dry weight of seeds, and dry weight of stems per polybag. Data were analyzed by ANOVA followed by the Least Significant Difference 5% test. The results of the study showed that there was a significant interaction of trichoderma biofertilizer and 5% moisture content on plant height at 7 days after planting, biological fertilizers had a significant effect on plant height 7 and 14 day after planting, stem diameter 7, 14, 21, 28 , 35, 42, 49 and 56 day after planting, also had a significant effect on seed dry weight and stover dry weight, water content had a very significant effect on plant height at 14 day after planting with the lowest 5% moisture content treatment.